Endoscopic versus surgical treatment for infected necrotizing pancreatitis: a systematic review and meta-analysis of randomized controlled trials - Haney, Caelán Max; Kowalewski, Karl-Friedrich; Schmidt, Mona Wanda; Koschny, Ronald; Felińska, Eleni Amelia; Kalkum, Eva; Probst, Pascal; Diener, Markus K.; Müller, Beat P.; Hackert, Thilo; Nickel, Felix (Surgical endoscopy and other interventional techniques, 2020)
To compare outcomes of endoscopic and surgical treatment for infected necrotizing pancreatitis (INP) based on results of randomized controlled trials (RCT).
Gesehen am 11.08.2021